Oral health status, oral health related quality of life and associated factors in patients with facial burns at the burn care centre, institute of medical sciences, Pakistan - Chaudhary, Farooq Ahmad (2020)
There was a limited understanding of the oral health conditions of facial burn victims. Hence, this study aimed to determine the oral health status, oral health-related quality of life and associated risks factors in a sample facial burn patient. This cross-sectional study had randomly and systematically recruited patients with facial burns in Islamabad, Pakistan. Extra and intra-oral examinations were carried out to measure the severity of disfigurement, caries, periodontal and oral hygiene statuses. The socio-demographic characteristics, self-perceived oral health status, oral health behaviours, oral health-related quality of life and psychosocial indicators were assessed using self-administered instruments in Urdu language. Burn injury characteristics were obtained from the medical records. Data were analysed using descriptive and linear regression analysis, and structural equation modelling. A total of 271 facial burn patients participated in the study. The majority were females (68.6%) and under 35-yearold (78.9%). About 48% had a third-degree burn, 46.1% had >20% total body surface area burned and 82.7% had sustained the injuries for more than 2 years. All of the participants had at least one carious tooth and the mean DMFT was 10.96 (sd = 2.41). About 60% had periodontitis and 66%, poor oral hygiene. The majority of participants perceived that their dental (79%) and periodontal (80%) health status was poor. About 78% brushed their teeth once daily and 89% did not visit the dentist regularly. The DMFT, CPI and OHI-S were associated with the burn characteristics and oral health behaviours (p<0.05). Psychological, cost of treatment and distance to the healthcare centre were the most cited main barriers to healthcare service utilisation. Multiple regression analysis showed that a greater burn severity, the longer time elapsed since the burn, age and psychological issues were associated with poorer oral health status and; more frequent tooth brushing and dental visit, with a better status (p<0.01). About 94% of the participants had at least one OHIP- 14 item impacted. Psychosocially, the majority of participants had low self-esteem (74.5%) and moderate to a high level of social support (95%) and showed a high level of anxiety and depression. More severe facial disfigurement, lower self-esteem, dissatisfaction with appearance, poorer social support and greater anxiety were associated with poor oral health status and oral health-related quality of life (p<0.05), but not for resilience and depression. The SEM analysis showed a pathway model that connected facial burn injury to oral health status, oral health-related quality of life and general quality of life. Burn injury was also related to psychosocial functioning, which then, linked to oral health status and quality of life. There was a direct and indirect effect of psychosocial functioning on oral health-related quality of life; the latter, via the oral health behaviours. In conclusion, this study suggests plausible evidence for the effect of facial burn on oral health. Depending on the severity, the injury changes the physical characteristics of facial features and makes oral healthcare maintenance to be more difficult. It also affects the psychosocial functioning of the victims which then adversely influence health behaviours. Together, they increase the risks of poor oral health outcomes and oral health-related quality of life.